Effect of Alginate and Polyethylene Glycol Addition on Physical and Mechanical Characteristics of k-Carrageenan-based Edible Film - Giyatmi, Giyatmi; Poetri, Tika Annisa Eka; Irianto, Hari Eko; Fransiska, Dina; Agusman, Agusman (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2020)
Waste disposal problems have attracted scientists around the world to explore the use of renewable resources to produce biodegradable films and coatings. Indonesia has diverse renewable resources of biopolymers that originated from seaweeds such as carrageenan, agar, and alginate. Carrageenan is considered as a potential biopolymer for edible film manufacture due to its characteristic range. This study aimed to develop carrageenan-based edible film using alginate and polyethylene glycol as plasticizers. Edible film made from k-carrageenan with the addition of alginate and polyethylene glycol (PEG) as plasticizers was tested for its mechanical properties, water vapor transmission rate (WVTR) and water solubility.Â Blending k-carrageenan with alginate (0%, 0.25%, 0.5%, 0.75%, and 1.0% w/v) increased tensile strength, thickness, and water solubility, but reduced elongation at break, WVTR, and moisture content. The addition of PEG (1%, 2%, and 3% w/v) reduced tensile strength and water solubility, but increased elongation at break, thickness, and moisture content. This study recommended that the best carrageenan-based edible film was obtained from a formula using 1% alginate (w/v) and 1% PEG (w/v).